A Self‐Catabolic Multifunctional DNAzyme Nanosponge for Programmable Drug Delivery and Efficient Gene Silencing. (31st March 2021) - Wang, Jing; Yu, Shanshan; Wu, Qiong; Gong, Xue; He, Shizhen; Shang, Jinhua; Liu, Xiaoqing; Wang, Fuan
Abstract: DNAzyme‐based gene therapy holds immense prospects for effectively treating severe diseases, yet is constrained with inefficient delivery and unconditional activation. Herein, we designed a bioinspired self‐catabolic DNA nanocapsule for sustaining tumor‐specific cascade activation of therapeutic DNAzyme. The exquisite DNAzyme was temporarily masked by the self‐excising DNAzyme in the hierarchical rolling circle replication (RCR) nanostructures, thus stayed in an inactive state in physiological fluids. Through the multivalent tumor‐anchoring aptamer strands, the RCR nanocapsule was specifically accumulated in cancer cells and was sequentially activated for motivating the ultimate DNAzyme‐mediated gene silencing via the intelligent stimuli‐responsive cascade DNAzyme activation. By virtue of the programmable RCR assembly strategy, our compact DNAzyme nanoplatform shows great promise for developing versatile smart gene therapeutics and personalized nanomedicines. Abstract : An exquisite cascade DNAzyme‐sustained gene silencing platform was assembled to program the „mask‐cleave‐release" of therapeutic DNAzyme from the intelligent DNAzyme nanosponge, where the upstream self‐catabolic DNAzyme mediated the specific and accurate activation of downstream therapeutic DNAzyme for guaranteeing the efficient gene silencing with improved bioavailability.